Pengaruh Citra Merek dan Harga terhadap Loyalitas Pelanggan Sparepart Mobil Payung Auto Solution - Ika Kartika (Jurnal Riset Rumpun Ilmu Ekonomi, 2025)
This research was conducted at Payung Auto Solution. The purpose of this study was to determine and analyze the influence of brand image and price on customer loyalty of paying auto solution. The population numbered 138 customers while the sample in this study were: which amounted to 102 customers. The sampling technique used is simple random sampling. Data collection techniques are by distributing questionnaires, interviews and documentation studies. Data analysis uses multiple linear regression analysis. The conclusion in the study that Brand Image has a positive and significant effect on customer loyalty of Payung Auto Solution Medan car spare parts. Price has a positive and significant effect on customer loyalty of Payung Auto Solution Medan car spare parts. Brand Image and Price have a positive and significant effect on customer loyalty of Payung Auto Solution Medan car spare parts. Adjusted R Square is: equal to 0.266 means Brand Image and Price can explain Customer Loyalty of 26.6% and the remaining 73.4% is influenced by other variables outside of this research such as: promotion, service, product innovation and so on.